When Tibetan Meditation Goes Global A Study of the Adaptation of Bon Religious Practices in the West - Arizaga, Mara Lisa (Welten Süd- und Zentralasiens / Worlds of South and Inner Asia / Mondes de l'Asie du Sud et de l'Asie Centrale, 2022)
This pioneering ethnographic work on Western practitioners of Bon, or bonpos, presents the first in-depth study of the transition of the Yungdrung Bon religion, Tibet's so-called indigenous religion, to the West in the context of globalization. It shows how Bon, including Dzogchen meditation, is lived by its followers in the West and how a particular religion expands and integrates into new cultural settings as a consequence of globalization.